Pemberdayaan Kelompok Sadar Wisata (POKDARWIS) dalam Pengembangan Desa Wisata Peneleh Kota Surabaya - Devani Pradipta Syaharani; Gracea Devina Subiantoro; Khusnia Nazila Irawati; Juliana, Wina; Manggalou, Singgih (Faculty of Social and Political Science, 2026)
Tourism is a strategic sector in national and regional economic development as it can create employment opportunities, increase community income, and promote the preservation of local culture. One effective approach in tourism development is through local community empowerment, as implemented in the concept of Community Based Tourism (CBT). This research examines the role of Tourism Awareness Groups (POKDARWIS) in community empowerment efforts in Peneleh Tourism Village, Surabaya City. Peneleh Tourism Village has high historical and cultural potential, such as the house of national figure H.O.S Tjokrominoto, Dutch cemetery, and traces of settlements since the 13th century. The Surabaya City Government through the Department of Culture, Youth, and Sports as well as Surabaya City Tourism has established and empowered POKDARWIS as the main driver in managing tourism potential based on community participation. This research uses a descriptive-qualitative approach with literature study and field observation methods. The study results show that POKDARWIS plays an active role in tour guide training, local product development, and digital promotion. Therefore, recommendations are focused on strengthening synergy between POKDARWIS, government, and other stakeholders to realize the sustainability of Peneleh Tourism Village as a leading community-based destination.